Improving morbidity and mortality in patients with pulmonary hypertension: insights from a nation-wide registry - Kaymaz, C.; Akbulut, M.; Basarici, I.; Yildirimturk, O.; Asker, M.; Kaya, E. B.; Tokgozoglu, L. (Oxford Univ Press, 2024)
[Abstract Not Available]
European-Society-of-Cardiology Congress (ESC) -- AUG 30-SEP 02, 2024 -- London, ENGLAND